BACTERIAL METABOLITES FROM BACILLUS CEREUS B4 RESPONSIBLE FOR POTATO PLANT GROWTH - Sunaina, V; Ajay, S.; Dureja, P (Potato Journal, 2013)
Bacillus cereus B4 a biocontrol agent, produces three types of metabolites that contribute to its ability to suppress certain plant diseases and promote growth of potato crop. The metabolites were identified as Kanosamine, 3,4-dihydroxy benzoate (also known as 3,4-DOHB), and 2 keto-4 methylthiobutyrate. To enhance understanding of biological activity related to plant growth promotion, mode of action of one metabolite namely, 3,4-DOHB was determined. The metabolite improved crop vigour by eliminating free radicals which provided conditions for development of larger and healthier root system.